2009
DOI: 10.1071/wf08117
|View full text |Cite
|
Sign up to set email alerts
|

Climate, lightning ignitions, and fire severity in Yosemite National Park, California, USA

Abstract: Continental-scale studies of western North America have attributed recent increases in annual area burned and fire size to a warming climate, but these studies have focussed on large fires and have left the issues of fire severity and ignition frequency unaddressed. Lightning ignitions, any of which could burn a large area given appropriate conditions for fire spread, could be the first indication of more frequent fire. We examined the relationship between snowpack and the ignition and size of fires that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 42 publications
8
90
2
Order By: Relevance
“…In forested areas, our high-severity category therefore generally describes a conversion of forest to a nonforested condition. For Yosemite, we augmented the severity data we had previously developed to match the size (.80 ha) and time period ) of the FS data (Collins et al 2009, Lutz et al 2009). The Yosemite fire severity database includes data for management ignited fires and wildfires that were either lightning or human caused.…”
Section: Datamentioning
confidence: 99%
“…In forested areas, our high-severity category therefore generally describes a conversion of forest to a nonforested condition. For Yosemite, we augmented the severity data we had previously developed to match the size (.80 ha) and time period ) of the FS data (Collins et al 2009, Lutz et al 2009). The Yosemite fire severity database includes data for management ignited fires and wildfires that were either lightning or human caused.…”
Section: Datamentioning
confidence: 99%
“…However, fires do not uniformly reduce carbon over the area within a fire perimeter-except in the most extreme high severity scenarios. Rather, there is a range of severities that produce a range of carbon loss to the atmosphere and transfer to the standing dead pool [31,[75][76][77]. Figure 6 presents a basic model of carbon fluxes immediately following wildfire and provides a computational framework for post-fire carbon loss accounting using fire severity data.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results do not suggest either a large or statistically significant effect of low-to moderate-severity fire. A more comprehensive assessment of the effects of fire on the landscape will require a consideration of fire severity [32,75], the proportionate area within a fire perimeter that remained unburned [78,79,82,83], and details on pre-fire and post-fire carbon accumulation rates [41,46,76]. .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that climate change will increase the size and frequency of wildfires in California, which is problematic for a state that already leads the nation in wildfire-related economic losses (Flannigan et al 2000;Lutz et al 2009;Westerling et al 2009 While the physical effects of fire on transmission lines is widely noted, it is more difficult to estimate the length of time that a line would be down in these cases, as these impacts can interrupt the line's service either momentarily or for an extended time period (CAISO 2009). It is even more difficult to relate these events to an actual outage, since the transmission system can often cope because of the redundancy intentionally built into the power system.…”
Section: Chapter 4: Projected Wildfire Risk To Electricity Transmissionmentioning
confidence: 99%